THE EFFECT OF PARENTAL SUPPORT AND DISCIPLINE LEVEL ON STUDY HABITS AND ITS IMPLICATIONS ON MATHEMATICS LEARNING OUTCOMES OF JUNIOR HIGH SCHOOL STUDENTS - Dini Wardani Maulida; Miftachul Hidayati; Ade Irmanopaliza; Nining Setyaningsih (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
The low mathematics learning outcomes of students in Indonesia are influenced by several factors, such as parental support, the level of discipline, and student study habits that still need to be improved. The purpose of this study is to examine the direct effect of parental support and discipline on study habits, the direct effect of the three variables on learning outcomes, and the indirect effect of parental support and discipline on learning outcomes through study habits. This research method is quantitative with a correlational design. The research subjects were 100 students in grades VII and VIII in one of the junior high schools in Purwodadi Regency from a total population of 150 students. Data collection techniques used questionnaires to measure parental support, discipline, and study habits, as well as math tests for learning outcomes. Data were analysed using path analysis with SPSS version 16, preceded by prerequisite tests (normality, linearity, multicollinearity, heteroscedasticity). The results showed that parental support and discipline had a significant effect on study habits (70% contribution), with discipline as the dominant factor. Only the level of discipline has a significant direct effect on learning outcomes (8.3% contribution). Parental support has a significant indirect effect on learning outcomes through study habits. Discipline is the main internal factor affecting learning habits and learning outcomes.